2006
DOI: 10.1248/cpb.54.262
|View full text |Cite
|
Sign up to set email alerts
|

COX-1, COX-2 Inhibitors and Antifungal Agents from Croton hutchinsonianus

Abstract: Croton hutchinsonianus HOSSEUS belongs to the family Euphorbiaceae. It is a shrub or small tree reaching 4-5 meters high and native to Thailand,1) where it is commonly called "Plao phae". In this paper, we describe the isolation and structure elucidation of newly isolated 3Ј-(4Љ-hydroxy-3Љ,5Љ-dimethoxyphenyl)-propyl benzoate, 3Ј-(4Љ-hydroxyphenyl)-propyl benzoate and four known compounds [3Ј-(4Љ-hydroxy-3Љ-methoxyphenyl)-propyl benzoate, poilaneic acid, farnesyl acetone and 4-hydroxybenzaldehyde] from the bran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 6 publications
0
21
1
Order By: Relevance
“…From the aerial parts of C. hutchinsonianus Hos., a species native in Thailand, two new compounds were isolated, namely 3'-(4"-hydroxyphenyl)-propyl benzoate and 3'-(4"-hydroxy-3",5"-dimethoxyphenyl)-propyl benzoate (23), together with the known 3'-(4"-hydroxy-3"-methoxyphenyl)-propyl benzoate. 130 Lignoids are common in plant groups bearing benzylisoquinolines and related alkaloids (derived biosynthetically from tirosine), such as Ranunculales and Magnoliales. As was commented above, some Croton species possess this class of alkaloids.…”
Section: Flavonoids and Other Phenolic Substancesmentioning
confidence: 99%
“…From the aerial parts of C. hutchinsonianus Hos., a species native in Thailand, two new compounds were isolated, namely 3'-(4"-hydroxyphenyl)-propyl benzoate and 3'-(4"-hydroxy-3",5"-dimethoxyphenyl)-propyl benzoate (23), together with the known 3'-(4"-hydroxy-3"-methoxyphenyl)-propyl benzoate. 130 Lignoids are common in plant groups bearing benzylisoquinolines and related alkaloids (derived biosynthetically from tirosine), such as Ranunculales and Magnoliales. As was commented above, some Croton species possess this class of alkaloids.…”
Section: Flavonoids and Other Phenolic Substancesmentioning
confidence: 99%
“…The IR spectrum exhibited absorption bands due to hydroxyl (3381, 3296 cm À1 ), conjugated carbonyl (1683 cm À1 ) and olen (1625 cm À1 ) functionalities. The 1 H and 13 C NMR spectroscopic data of 14 (Experimental section and Table 2) were similar to those of 13, except for changes at CH [2][3][4][5][6]1H,dd,J ¼ 13.6,4.4 Hz,d H 2.11,1H,d,J ¼ 13.6 Hz;d C 29.0), 1H,d,J ¼ 4.0 Hz;d C 62.3),, and C-9 (d C 162.4). These data suggested that a hydroxyl group should be bonded to C-7 and a double bond was at C-8.…”
Section: Resultsmentioning
confidence: 64%
“…The 1 H-1 H COSY experiment showed connectivity of three moieties: I: 1 CH 2 -2 CH 2 -3 CH 2 ; II: 5 CH-6 CH 2 -7 CH 2 ; and III: 9 CH-11 CH(O)-12 CH 2 . The HMBC correlations from CH 3 -19 (d H 0.79, 3H, s) to C-3 (d C 35.1), C-5 (d C 44.4), and C- 18 (d C 15.7); from H [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]each 1H,d,J ¼ 11.2 Hz) to C-3, C-5, and C-19 (d C 17.7); and from H 2 -2 (d H 1.50 and 1.60, each 1H, m) to C-4 (d C 37.5) indicated that C-4 connected units I and II together. The HMBC correlations from CH 3 -20 (d H 0.96, 3H, s) to C-1 (d C 41.4), C-5, and C-9 (d C 66.0) and from H 2 -1b (d H 0.96, 1H, m) to C-9 suggested that C-10 (d C 35.9) connected units I and III together.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations